PENGARUH KONSERVATISME AKUNTANSI DAN GOOD CORPORATE GOVERNANCE PADA KUALITAS LABA - Tuwentina, Putu; Wirama, Dewa Gede (E-Jurnal Akuntansi, 2014)
Earnings quality is one of information that affects the stakeholders in making decisions about the company. To analyze the quality of earnings disclosed by the company, it is important to know the factors that affect the quality of earnings. This study was conducted at the companies listed on the Indonesian Stock Exchange and the Corporate Governance Perception Index rating agency or CGPI in 2008-2012. Samples were obtained by 55 by purposive sampling method . The technique of data analysis used is multiple linear regression analysis. proxy for earnings quality measure used is ERC, accounting conservatism measured by the conservatism index , and GCG measured by CGPI index. The results showed that the positive effect of accounting conservatism on earnings quality. So that, companies that use accounting conservatism get a positive response from investors based on earnings presented. Another variable that good corporate governance does not affect the quality of earnings.
Keywords: accounting conservatism , CGPI, ERC